Kolaborasi Perguruan Tinggi Dan LAZ Dalam Upaya Pencegahan Stunting - Indri Yuliafitri; Nabela Hapsari; Ahmad Luqman Hakim (CV. Multi Kreasi Media, 2026)
Stunting remains a chronic nutritional problem that affects the quality of human resources in Indonesia, particularly among toddlers and pregnant women. Low nutritional literacy and limited access to nutritious food are the main contributing factors. This community service activity aims to increase public awareness of stunting and provide direct intervention through Supplementary Feeding Programs. The activity was carried out through collaboration between the Islamic Economics Study Program of Universitas Padjadjaran and LAZ Al Hilal. The implementation methods included educational socialization on stunting, interactive discussions, and the distribution of supplementary food for toddlers and pregnant women. The results indicate an increase in participants' understanding of stunting prevention and strong community engagement. This program is expected to serve as a collaborative model between universities and zakat institutions in supporting community-based stunting reduction efforts.